The RNA-seq approach to discriminate gene expression profiles in response to Beauveria bassiana and Micrococcus luteus microbial pathogens on Actias selene (Lepidoptera: Saturniidae) - Liang, Dan; Wang, Pei; Wu, Lingling; Jiang, Xiaoli; Wei, Guoqing; Zhu, Baojian; Wang, Lei; Zhang, Heyu; Toufeeq, Shahzad; Qian, Cen; Liu, Chaoliang (Zootaxa, 2019)
Actias selene (Hübner) is an important silk-spinning moth. Like other moths, it has innate immunity but no acquired immunity. However, there are few studies on immune-related genes of A. selene. Here, differential expression RNAseq experiment was employed to examine the genes related to different metabolic pathways and to explore the immune mechanism of the A. selene post Beauveria bassiana (Bb) and Micrococcus luteus (ML) stimuli. A total of 64,372,921 clean reads were obtained and 39,057 differentially expressed genes (DEGs) were identified. In the Bb vs. PBS group (PBS as the control), 9,092 genes were up-regulated and 4,438 genes were down-regulated; in the ML vs. PBS group, 5,903 genes were up-regulated and 5,175 genes were down-regulated. The KEGG (Kyoto Encyclopedia of Genes and Genomes) and GO (Gene Ontology) analyses of DEGs confirmed that many DEGs were associated with "Metabolism pathway", "cellular process", "cell" and "catalytic activity". Among them, 194 and 149 differentially expressed genes were related to immunity in the Bb vs. PBS group and ML vs. PBS group, respectively. We verified the reliability of the data with reverse transcription quantitative real-time PCR analysis of randomly selected genes. Furthermore, the phylogenetic tree results showed that HSP90, PGRP and MyD88 genes of A. selene were most closely related to Antheraea pernyi (Guérin-Méneville). These results will provide an overview of the molecular mechanism of A. selene resistance to fungal and bacterial infections as well as an evolutionary aspect of these genes. Moreover, the interrelated trophic mechanisms among different groups of organisms are vital to explore, thus this study will lay a foundation for further studies on the innate immune mechanism of saturniid moths, and provide important theoretical basis for studying the relationship between A. selene and other species.